Buddhist Philosophy in Education: Enhancing Critical Thinking, Compassion, and Cognitive Development in Nepal - Nirajan Bohara MPhil Scholar (Lembaga Penelitian Dan Publikasi Ilmiah (lppi) Yayasan Almahmudi Bin Dahlan, 2026)
This study examines Buddhist philosophy in Nepal’s diverse educational landscape where ethical, moral, and logical appeals are an urgency of 21st century skills. It is the background of holistic, ethical growth in Nepali education context. The main objective of this paper is to explore critical thinking, emotional stability, mindfulness of Buddhist philosophy in the Nepali education system. The concept of mindfulness andcompassion highlights canonical teachings. I employed a qualitative descriptive approach using thematic analysis. Primary and secondary sources were used to formulate themes. Moreover, I applied Piaget’s theory of cognitive development and Buddhist philosophical perspective to view cognitive, social, cultural, and psychological dimensions. It focuses on how Buddhism can be the practice of education assimilating holistic, academic, and moral development. Findings highlight the Buddha’s wisdom as a framework for education, Buddhist pedagogy, mindfulness, classroom practice, moral, engagement, respectful learning environment, challenges, and implications of integrating Buddhism into education. Buddhist philosophy creates value-driven and interactive motive in education. The study highlights Buddhist principles that reveal ethical insights and enlightenment in education. Challenges show resource limitations, traditional knowledge systems, and secular constraints. Intrinsic motivation fosters with the help of meditation, mindfulness, and the role of interpersonal ethics. Teachers are encouraged to integrate Buddhist methods for role play and reflective discussion in classrooms. This paper underscores academic excellence, emotional stability, and fostering critical thinking, empathy, and socio-cultural insights in the settings of multiethnic and multireligious nation Nepal. This paper recommends reflective discussion, mindfulness, meditation, empathy, and guidance towards compassion.